Effect and Mechanism of Probiotics in Alleviating or Treating Inflammatory Bowel Disease - Kang XU; Zhe WANG; Zhipeng XUE; Jiapeng WANG; Zhenshang XU; Ting WANG (Shipin gongye ke-ji, 2022)
Inflammatory bowel disease (IBD), gradually increasing in China, is a chronic and recurrent intestinal inflammatory disease. Recently, probiotics have been applied for the treatment of IBD, and some probiotic strains can alleviate or treat IBD by protection of the intestinal barrier and regulating expression of immune and inflammatory factors. Meanwhile, probiotics have the characteristics of good tolerability and few adverse reactions, resulting in their commonness in the clinical application of IBD treatment. This article mainly introduces the research progress of probiotics in the treatment of IBD, including the classification, mechanism of action and clinical research.